Urban design of clusters oriented towards the creative economy in Barquisimeto city (Gaceta Técnica, 2026)
The purpose of this paper was the urban design of clusters oriented toward the creative economy in the city of Barquisimeto. The selected study area is bounded to the north by Libertador Avenue, to the south by Carrera 14, to the east by Calle 17, and to the west by Carabobo Avenue/Calle 29. The design process took into account the area's urban characteristics, identifying zones with potential for the creation of creative clusters as well as the lines and levels of intervention. This culminated in the CC17 Master Plan, which is characterized by pathways featuring distinct textures and street furniture, the categorization of individual clusters, and a functional layout that serves as a model
Keywords: creative cluster; urban design; CC17 master plan